HALAL AS SOCIAL CAPITAL: A STUDY ON ECONOMY AND IDENTITY - Khairil Anwar; Ari Yunanda M Husen (Jurnal Analisa Sosiologi, 2025)
This study explores the role of the halal concept as social capital in shaping the economic identity of Muslims in the globalization era. Using a qualitative literature review approach, the study maps relevant literature related to the transformation of halal values and Muslim consumer behavior. The findings reveal three main dimensions. First, the halal concept has evolved from a mere religious obligation into a symbolic capital that adds value to products in the global market while strengthening the collective identity of Muslims. Second, within Pierre Bourdieu's theoretical framework, halal functions as symbolic capital that provides social legitimacy, economic differentiation, and reinforces new hierarchies in the global market. Third, Putnam's theory explains how halal practices build solid social networks through a combination of bonding and bridging capital, fostering trust among producers, consumers, and certification bodies. Halal contributes not only to the sustainability of the global halal industry but also promotes the creation of a more ethical and inclusive business ecosystem. This research provides new perspectives on how the halal concept functions as social capital, reinforcing global economic dynamics while supporting the sustainable growth of the halal market.